2013
DOI: 10.1093/mutage/get007
|View full text |Cite
|
Sign up to set email alerts
|

Association of P2X7R gene polymorphisms with systemic lupus erythematosus in a Chinese population

Abstract: The P2X7 receptor is a ligand-gated cationic channel receptor that is actived by ATP and normally expressed by a variety of immune system cells, including macrophages and lymphocytes. Because it leads to release of IL-1β and cell death by apoptosis or necrosis, it is a potential therapeutic target for a variety of autoimmune inflammatory diseases, such as systemic lupus erythematosus (SLE). The P2X7R gene is highly polymorphic, and many single-nucleotide polymorphisms (SNPs) have been detected. A case-control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 35 publications
0
22
3
Order By: Relevance
“…In our previous study, we found the following genotype frequencies in SLE patients and healthy controls, respectively: AA genotype frequency in 1068G>A, 0.670 and 3.430%; CC genotype frequency in 1513A>C, 4.160 and 5.025%; GG genotype frequency in 1096C>G, 3.005 and 2.771%, all of which are very low [24]. In the current study, we did not identify the above genotypes in the chosen subjects.…”
Section: P2x7r Expression and Cytokine Levels In Patients With Differcontrasting
confidence: 67%
See 1 more Smart Citation
“…In our previous study, we found the following genotype frequencies in SLE patients and healthy controls, respectively: AA genotype frequency in 1068G>A, 0.670 and 3.430%; CC genotype frequency in 1513A>C, 4.160 and 5.025%; GG genotype frequency in 1096C>G, 3.005 and 2.771%, all of which are very low [24]. In the current study, we did not identify the above genotypes in the chosen subjects.…”
Section: P2x7r Expression and Cytokine Levels In Patients With Differcontrasting
confidence: 67%
“…Similarly, in our previous studies, we did not identify an association of the above SNPs with SLE development. Rather, we found that the 1068G>A polymorphism was associated with SLE development [24], suggesting that dysregulated P2X7R gene expression and function was involved in the development of SLE. The P2X7R gene SNP 1068 G>A changes the alanine to threonine at amino acid 348 and leads to a gain-of-function effect and enhanced IL-1β secretion [18].…”
Section: Introductioncontrasting
confidence: 55%
“…A loss-of-function (1513 A>C) SNP of the P2X7R gene affects ATP-induced cellular functions such as apoptotic cell death (10) and IL-1β release (11). More evidence to support the intimate relationship of P2X7R gene polymorphisms with autoimmune diseases are the demonstrated links between P2X7R polymorphisms and RA and systemic lupus erythematosus (SLE) (1213). However, there are no available data linking P2X7R SNPs with gout.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, no significant association of rs208294 and rs2230911 SNPs with RA or SLE was previously reported, but individuals with genetic variation in rs208294 revealed a higher ethidium bromide absorption in response to ATP than rs2230911 polymorphism 21. Chen et al suggested that rs2230911 SNP was associated with lupus nephritis susceptibility, where G allele was associated with a lower risk of lupus nephritis 12. The rs3751143 changes glutamic acid into alanine at residue 496 (Glu496Ala) in the carboxyl terminus of the receptor, which causes reduced receptor activity 23.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, rs208294 allele in patients with chronic lymphocytic leukaemia was expected to increase P2 X 7 R function in peripheral blood lymphocytes depending on the combined presence of loss-of-function variants 21. Variations of rs2230911 can also change aminoacids coding (Ser 357 to Thr), which was associated with a partial function loss of P2 X 7 R through affecting channel and pore function,12 and the MAF of rs2230911 in Chinese population is 0.244 22. It was indicated that rs2230911 may impact mycobacterial killing induced through ATP in macrophages, but it was not associated with SLE in Chinese patients 22.…”
Section: Discussionmentioning
confidence: 99%